Strategies to reduce disordered eating among female athletes: A working paper
This position statement is based on a comprehensive review and interpretation of scientific literature concerning body composition assessment, disordered eating and the Female Athlete Triad. Because this is a work-in-progress this draft position statement has not yet been submitted to nor endorsed by the board of the Canadian Academy of Sport Medicine.